2017
DOI: 10.1097/j.pain.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam as an active placebo in 3 fentanyl-validated nociceptive pain models

Abstract: The use of inactive placebos in early translational trials of potentially analgesic compounds is discouraged because of the side-effect profiles of centrally acting analgesics. Therefore, benzodiazepines are used, although their use has not been validated in this context. Whether benzodiazepines confound the results of acute pain tests is unknown. Midazolam (0.06 mg/kg) as an active placebo was investigated in 3 nociceptive models that included contact heat, electrical pain, and pressure pain thresholds in 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, systemic administration has resulted in hyperalgesic effects in both rats [ 9 ] and humans [ 6 , 10 , 11 ]. Moreover, the evidence is conflicting, with a few other human studies claiming that systemic midazolam is analgesic [ 7 , 12 , 13 ], while others found no effect on pain [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, systemic administration has resulted in hyperalgesic effects in both rats [ 9 ] and humans [ 6 , 10 , 11 ]. Moreover, the evidence is conflicting, with a few other human studies claiming that systemic midazolam is analgesic [ 7 , 12 , 13 ], while others found no effect on pain [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%